2007
DOI: 10.1016/j.jvs.2007.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of type II endoleak with a transcatheter transcaval approach: Results at 1-year follow-up

Abstract: TTE appears to be a feasible technique for the complete exclusion of type II endoleaks. Technical and clinical successes are comparable with other treatment strategies, and TTE should be considered an alternative to direct translumbar puncture of the aneurysm sac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…Furthermore, with TCE, the IVC is punctured through one wall instead of both, as required when the right translumbar/transcaval approach is performed, and lower risk of retroperitoneal hemorrhage or inadvertent bowel injury may be anticipated. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with TCE, the IVC is punctured through one wall instead of both, as required when the right translumbar/transcaval approach is performed, and lower risk of retroperitoneal hemorrhage or inadvertent bowel injury may be anticipated. 6 …”
Section: Discussionmentioning
confidence: 99%
“…6 The focus of this report is to describe our experience with TCE and to highlight the technical conduct of the procedure.…”
mentioning
confidence: 99%
“…The literature is replete with multiple suggested routes of T2EL ablation, including laparoscopic ligation of the inferior mesenteric artery, 13 concurrent operative lumbar embolization, 14,15 post-EVAR embolizations, 16,17 and post-EVAR operative approaches. 18 Previously, our institutional experience has shown that continued observation of persistent T2EL with stable aneurysm sac size is both safe and cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been described to treat these endoleaks, including transarterial, transcaval, and translumbar approaches. [94][95][96] Type II endoleaks occur in 10% to 30% of patients after EVAR and may be associated with aneurysm growth and rupture. Subdivision of type II endoleaks into transient (resolving within 6 months) and persistent (present beyond 6 months) has been found to predict EVAR-related complications.…”
Section: April 7 2015mentioning
confidence: 99%